Philo of Alexandria and post-Aristotelian philosophy - Alesse, Francesca (Studies in Philo of Alexandria ;, 2008)
Focuses on the role played by the philosophy of the Hellenistic, or post-Aristotelian age in Philo of Alexandria's works. This inquiry draws on the presence of Hellenistic philosophy in Philo and provides a better knowledge of the diffusion of Hellenistic philosophy since the late Republican age.